Cloning and Characterization of the Murine Coagulation Factor X Gene - Cooper, Adrian; Liang, Zhong; Castellino, Francis J.; Rosen, Elliot D. (Thrombosis and Haemostasis, 2000)
The gene encoding murine coagulation factor X (fX) was isolated and characterized from a λFIX II library generated from murine genomic DNA. The 20130 bp sequence contains 18049 nucleotides that extend from the initiating methionine to the polyadenylation site. 1056 nucleotides 5’ of the start codon were determined and contain putative start sites for the FX mRNA as well as sites for binding of putative transcription factors. The sequence extends 1024 3’ of the polyadenylattion site.The gene contains 8 exons and 7 introns which were determined by comparing the mouse FX cDNA and gene sequences. The exonic structure of the gene is similar to that of the other mammalian vitamin K-dependent serine proteases of the coagulation system. These include an exon encoding the prepropepetide, the gladomain, a short helical stack, two exons for the two EGF domains, the activation pepetide, and two exons encoding the serine protease domain. The 5’ sequence of the mouse FX gene overlaps with the 3’ region of the FVII gene indicating that the murine FVII and FX gene are arranged in a head to tail arrangement as they are in humans.Abbreviations: fVII, coagulation factor VII; fIX, coagulation factor IX; fX, coagulation factor X; PC, Protein C; fV, coagulation factor V; fVa, activated coagulation factor V; fVIII, coagulation factor VIII; fVIIIa, activated coagulation factor VIII.
Keywords: Factor X; coagulation; gene; mouse; hemostasis